Are Government Spending Multipliers Greater during Periods of Slack? Evidence from Twentieth-Century Historical Data - Owyang, Michael T; Ramey, Valerie A; Zubairy, Sarah (American Economic Review, 2013)
A key question that has arisen during recent debates is whether government spending multipliers are larger during times when resources are idle. This paper seeks to shed light on this question by analyzing new quarterly historical data covering multiple large wars and depressions in the United States and Canada. Using Jorda's (2005) method for estimating impulse responses, we find no evidence that multipliers are greater during periods of high unemployment in the United States. In every case, they are below unity. We do find evidence of higher multipliers during periods of slack in Canada, with some multipliers above unity.